The Impact of Post-9/11 Fear and Prejudice on Legal Ethics and Human Rights: A Thematic Analysis of The Mauritanian 2021 (by Kevin Macdonald ) - GUELLOULA,Naima; Guellil, Assia (Faculty of Letters and Foreign Languages Department of English, 2025)
Thepost-9/11era ischaracterizedby fear,prejudice, and theU.S. waragainst terror,which led theAmerican government to overstep the boundaries of human rights and legal ethics. This study focuses on the Islamophobic reactions to the 9/11 attacks, the Western policy against terror, and how it affected the lives of innocent people who were detained without charges in Guantanamo Bay, in disregard of international law. The research adopts a qualitative thematic analysis approach in examining T h e M a u rit a n i a n as a case study. The film is based on the diary of Mohamedou Ould Slahi, documenting his experience in GuantanamoBayandhislegaljourneywithNancyHollanderindefendinghim